Function and Regulation of the C4-Dicarboxylate Transporters in Campylobacter jejuni - Wösten, Marc M. S. M.; van de Lest, Chris H. A.; van Dijk, Linda; van Putten, Jos P. M. (Frontiers in Microbiology, 2017)
C4-dicarboxylates are important molecules for the human pathogen C. jejuni, as they are used as carbon and electron acceptor molecules, as sugars cannot be utilized by this microaerophilic organism. Based on the genome analysis, C. jejuni may possess five different C4–dicarboxylate transporters: DctA, DcuA, DcuB and two homologues of DcuC. Here, we investigated the regulation and function of various C4–dicarboxylate transporters in C. jejuni. Transcription of the dctA and dcuC homologues is constitutive, while dcuA and dcuB are both directly regulated by the two-component RacR/RacS system in response to limited oxygen availability and the presence of nitrate. The DctA transporter is the only C4-dicarboxylate transporter to allow C. jejuni to grow on C4-carbon sources such as aspartate, fumarate, and succinate at high oxygen levels (10% O2) and is indispensable for the uptake of succinate from the medium under these conditions. Both DcuA and DcuB can sequester aspartate from the medium under low-oxygen conditions (0.3% O2). However, under these conditions, DcuB is the only transporter to secrete succinate to the environment. Under low-oxygen conditions, nitrate prevents the secretion of succinate to the environment and was able to overrule the phenotype of the C4-transporter mutants, indicating that the activity of the aspartate–fumarate–succinate pathway in C. jejuni is strongly reduced by the addition of nitrate in the medium.